Práticas pedagógicas com pensamento computacional no Programa Institucional de Bolsas de Iniciação à Docência (PIBID) no curso de pedagogia - Oliveira, Cheila Raiane Menezes (2024)
In contemporary society, mediated by the emergence of the skills development linked to computing, Computational Thinking has gained increasing visibility, with an emphasis on educational processes. With Resolution No. 1, of October 4, 2022, which deals with the National Common Core Curriculum (BNCC) for Computing, Computational Thinking gained emphasis alongside themes of the digital world and digital culture, which promotes focus in normative documents for the discussion of these themes in basic education. However, given this context, there is a need for discussions focused on teacher training, especially within Pedagogy courses, since these professionals will work directly in the early years of primary education. Thus, we analyze the importance of rethinking the practices developed in the university environment, in order to meet the formative demands of Computational Thinking with undergraduates. Therefore, the aim of this research is to investigate the pedagogical practices with Computational Thinking developed by Pedagogy undergraduates, within the scope of the Institutional Teaching Initiation Scholarship Program (PIBID) in the early years of elementary school. The research question is centered on the following premise: how does training in Computational Thinking in PIBID workshops enable pedagogical practices in the early years of elementary school, with Pedagogy undergraduates from the Federal University of Sergipe - Professor Alberto Carvalho Campus? The methodological approach adopted is based on qualitative research, which is grounded in the epistemology of the Theory of Everyday Research, based on Certeau (1997), Alves, Ferraço and Soares (2017). The cultural practitioners in this research are Pedagogy course scholarship holders, members of the Institutional Teaching Initiation Scholarship Program, linked to the Federal University of Sergipe (UFS), campus in the city of Itabaiana, Sergipe. The devices used in the research initially consisted of formative meetings to create practices related to Computational Thinking. These meetings took place in person at the university campus and online through Moodle and Blog. Finally, the data was produced through the device of conversation wheels and memories and analyzed through the procedure of interpretative analysis of the data produced in/with the field, in which two Subsuming Notions emerged, These were “Networks of Knowledge in Everyday School Life Woven with Teaching Initiation Scholars” and “Practices with Computational Thinking (un)plugged into Different Everyday Lives”, which were woven by the complexity of the phenomena included in the research, in which they pointed to Computational Thinking as a skill that is not limited to institutionalized educational spaces and the need to rethink the initial training curricula in the Pedagogy course, associating knowledge with Computational Thinking.